Compliance with ivory trade regulations in the United Kingdom among traders. Issue 4 (15th March 2019) - Harris, Lindsey; Gore, Meredith; Mills, Morena
Abstract: Global demand for elephant ivory is contributing to illegal poaching and significant decline of African elephant (Loxondonta africana) populations. To help mitigate decline, countries with legal domestic ivory markets were recommended by the Convention on International Trade in Endangered Species of Wild Fauna and Flora to close domestic markets for commercial trade. However, implementing stricter regulations on wildlife trade does not necessarily mean compliance with rules will follow. Using an online questionnaire, we examined the relationship between self‐reported compliance with ivory trade regulations among 115 ivory traders in the United Kingdom and 4 dimensions (control, deterrence, legitimacy, and social norms) hypothesized to influence compliance with conservation regulations. Although most traders supported regulations, a large number did not always check that they comply with them when trading objects containing ivory. The main factors influencing compliance with ivory trade regulations were traders' ability to comply and their perceptions of the regulations and punishments to deter illegal trade. These findings demonstrate the utility of conservation criminology to improve wildlife trade regulations and identify opportunities to reduce illegal ivory entering the market in the United Kingdom. Compliance could be improved by clearer regulations that facilitate easier detection of illegal ivory products and stronger prosecution of violations. Abstract : Article impact statement : Traders' compliance could be improved by clearer regulations that facilitate easier detection of illegal ivory and stronger prosecution. Abstract : Cumplimiento de las Regulaciones del Mercado de Marfil entre Comerciantes del Reino Unido Resumen: La demanda mundial por el marfil de elefante está contribuyendo a la caza ilegal y a la declinación significativa de la población del elefante africano (Loxondonta africana). Para ayudar a mitigar la declinación, la Convención sobre el Comercio Internacional de Especies Amenazadas de Fauna y Flora Silvestres recomendó a los países que tienen mercados domésticos legales de marfil que cierren estos mercados al intercambio comercial. Sin embargo, la implementación de regulaciones más estrictas sobre el mercado de fauna no significa necesariamente que después existirá un cumplimiento de las reglas establecidas. Examinamos con un cuestionario en línea la relación entre el cumplimiento auto‐reportado y las regulaciones del mercado de marfil de 115 comerciantes de marfil en el Reino Unido y cuatro dimensiones (control, disuasión, legitimidad y normas sociales) que creemos influyen sobre el cumplimiento de las regulaciones de conservación. Aunque la mayoría de los comerciantes respaldó las regulaciones, un gran número no marcó en la encuesta si cumplían con ellas cuando comercializaban con marfil. Los factores principales que influyen sobre el cumplimiento de las regulaciones del mercado de marfil son la aptitud del comerciante para cumplir y las percepciones que tiene de las regulaciones y los castigos para disuadir el comercio ilegal. Estos resultados demuestran la utilidad de la criminología de la conservación para mejorar las regulaciones del comercio de fauna e identificar las oportunidades para reducir la entrada de marfil ilegal al mercado del Reino Unido. El cumplimiento de las regulaciones podría incrementarse por medio de regulaciones más claras que faciliten la detección de productos ilegales de marfil y seguimiento más fuerte de las violaciones. 摘要: 全球范围内对象牙的需求导致了对非洲象 (Loxondonta africana) 的非法偷猎及其种群数量的显著下降。为减缓这一趋势, 《濒危野生动植物种国际贸易公约 (CITES) 》建议允许在国内合法交易象牙的国家关闭国内的象牙商业贸易市场。然而, 对野生动植物贸易执行了更严格的法规也并不一定意味着法规会得到遵守。我们通过在线问卷调查, 分析了英国一百一十五名象牙贸易商自我报告的对象牙贸易法规的遵守情况与被认为会影响对保护法规遵守情况的四个维度 (控制、威慑、合法性和社会规范) 之间的关系。研究发现, 虽然大多数贸易商都声称支持这些法规, 但许多人在交易含有象牙的商品时, 并不总是检查自己是否遵守了这些法规。影响象牙贸易法规遵守情况的主要因素是贸易商遵守法规的能力, 以及他们对防止非法贸易的法规和惩罚措施的认识程度。我们的研究结果表明, 保护犯罪学的应用有助于改进野生动植物贸易法规、找到减少非法象牙制品进入英国市场的机会。制定更明确的法规有助于更好地发现非法象牙制品、更有效地起诉违规行为, 从而促进对法规的遵守。【翻译: 胡怡思; 审校: 聂永刚】